Modeling of heat and mass transfer in a non-conventional rotary dryer. (5th January 2021) - Souza, G.F.M.V.; Avendaño, P.S.; Francisquetti, M.C.C.; Ferreira, F.R.C.; Duarte, C.R.; Barrozo, M.A.S.
Highlights: Heat and mass transfer between air and soybean seeds in a novel dryer was investigated. A two-phase model, with an appropriate set of constitutive equations, was used. The simulated results were in a good agreement with the experimental data with low deviations. The seeds quality was measured and related to the operating variables. Abstract: This study analyzed the simultaneous heat and mass transfer between soybean seeds and the air in a non-conventional rotary dryer developed by our research group, named as roto-aerated dryer. A two-phase model, with an appropriate set of constitutive equations, was used to describe the drying process. The system of equations was numerically solved using the normal collocation technique. The simulated results shown good agreement with the experimental data. The average difference between experimental and simulated results was of 1.5% for seed moisture content and of 6.3% for soybean temperature.